2022
DOI: 10.3390/polym14040828
|View full text |Cite
|
Sign up to set email alerts
|

Cassava Starch-Based Thermo-Responsive Pb(II)-Imprinted Material: Preparation and Adsorption Performance on Pb(II)

Abstract: Heavy metal pollution is currently an increasing threat to the ecological environment, and the development of novel absorbents with remarkable adsorption performance and cost-effectiveness are highly desired. In this study, a cassava starch-based Pb(II)-imprinted thermo-responsive hydrogel (CPIT) had been prepared by using cassava starch as the bio-substrate, N-isopropyl acrylamide (NIPAM) as the thermo-responsive monomer, and Pb(II) as the template ions. Later, a variety of modern techniques including FTIR, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The results showed that the adsorption and desorption processes of the imprinted polymers could be controlled by changing the solvent type. Traditional ICMs respond to the external environment only by adding responsive monomers in the polymerization process, such as N‐Isopropyl acrylamide (NIPAM), 22 p ‐phenylazoacrylanilide (PhAAAn), 23 2‐allyl‐1,3‐diphenylpropane‐1,3‐dione (ADPD), 20 N,N′‐(ethane‐1,2‐diyl)bis(2‐methylacrylamide) (EBMA), 24 and so on. But the above problem cannot be solved well due to the random copolymerization and the limited movement of responsive monomers in the rigid mesh structure.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the adsorption and desorption processes of the imprinted polymers could be controlled by changing the solvent type. Traditional ICMs respond to the external environment only by adding responsive monomers in the polymerization process, such as N‐Isopropyl acrylamide (NIPAM), 22 p ‐phenylazoacrylanilide (PhAAAn), 23 2‐allyl‐1,3‐diphenylpropane‐1,3‐dione (ADPD), 20 N,N′‐(ethane‐1,2‐diyl)bis(2‐methylacrylamide) (EBMA), 24 and so on. But the above problem cannot be solved well due to the random copolymerization and the limited movement of responsive monomers in the rigid mesh structure.…”
Section: Introductionmentioning
confidence: 99%